1996
DOI: 10.1046/j.1365-2958.1996.457984.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel peptidoglycan‐linked lipoprotein (ComL) that functions in natural transformation competence of Neisseria gonorrhoeae

Abstract: A novel peptidoglycan-linked lipoprotein (ComL) has been identified which is required for efficient transformation of Neisseria gonorrhoeae by species-related DNA. Although most mutations in comL appear to be lethal, transposon shuttle mutagenesis was successful in generating a single viable comL mutant of N. gonorrhoeae strain MS11. This mutant, N457, exhibits a cratered and crinkled colony morphology and grows slower than wild-type MS11. However, as indicated by electron microscopy, this retardation is due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 55 publications
0
68
0
Order By: Relevance
“…Interestingly, we found that BamD was not essential in Salmonella, unlike its homologue in E. coli (Malinverni et al, 2006;Onufryk et al, 2005), and its homologue in Neisseria gonorrhoeae, in which total deletion of comL (the bamD homologue) failed (Fussenegger et al, 1996). This constitutes the main difference between the BAM complex of Salmonella and that of E. coli.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, we found that BamD was not essential in Salmonella, unlike its homologue in E. coli (Malinverni et al, 2006;Onufryk et al, 2005), and its homologue in Neisseria gonorrhoeae, in which total deletion of comL (the bamD homologue) failed (Fussenegger et al, 1996). This constitutes the main difference between the BAM complex of Salmonella and that of E. coli.…”
Section: Discussionmentioning
confidence: 86%
“…In addition to the requirement for the expressions of pili (22,54), other proteins have been shown to have a role in natural transformation in the Neisseria spp. These include Tpc, mutants of which form tetracocci deficient in epithelial cell invasion and competence (23); ComA, an inner membrane protein which may be involved in translocation of DNA into the cytoplasm (19); ComL, a peptidoglycan-bound lipoprotein, mutants of which are significantly decreased in transformation (24); and PilT, which is involved in twitching motility and DNA uptake (63). Our results indicate that dca is also essential for transformation in gonococci.…”
Section: Discussionmentioning
confidence: 88%
“…However, even in the closely related bacterium Salmonella enterica, BamD appears to be dispensable (Fardini et al, 2009). Also, in Neisseria gonorrhoeae, a viable knockout mutant in the bamD homologue, designated comL, has been described (Fussenegger et al, 1996) but the gene appears essential for viability and OMP assembly in N. meningitidis (Volokhina et al, 2009). Thus, the Bam complex in bacteria consists of one essential central component, Omp85/BamA, and a variable number of accessory components, the importance of which is variable and depends on the specific component and the bacterium being studied.…”
Section: The Bacterial Omp Assembly Machinerymentioning
confidence: 99%